Tertúlia Dialógica Pedagógica: formação permanente do professorado com base em evidências científicas - Silva, Vivian Massullo (Universidade Federal de São Carlos, 2023)
The permanent and continuous training of teachers is a field of study that relates to different areas of knowledge based on ideological, political, social, epistemological and philosophical conceptions. In this work, the terms: permanent education and continuing education are purposely used together to demarcate the theoretical position in Freire (2015). The training movement based on scientific evidence has appeared in the reports of international organizations that directly relate the improvement of education with the quality of teacher training. Proven to be effective in the permanent and continuous formation of teachers, the dialogic Pedagogical Gathering (TDP) is a Successful Educational Action (CREA, 2015) and shows itself as a viable alternative for the dialogic formation of teachers in Brazil that seeks to unite with scientific knowledge, promoting improvement in the knowledge and social relationships of the entire school community. This doctoral thesis is based on the following research question: Can Dialogical Pedagogical Gatherings, as a dialogic training of teachers, contribute and in what way to the permanent and continued training of teachers based on scientific evidence in Brazil? As a general objective, we analyze, through transforming or excluding elements reported by the research participants, how the Dialogic Pedagogical gathering can be inserted in the context of permanent and continuous formation of teachers in Brazil, contributing to a permanent and continuous formation based on scientific evidence. Based on the framework of the Communicative Methodology (GÓMEZ et al., 2006), the investigation involved a total of 11 teachers from different regions of Brazil. To collect and deepen the data, focus groups and communicative reports were carried out. The investigation listed transforming and excluding elements in 5 categories: permanent and continuing education in the current context of teachers; the pedagogical dialogical gathering in the permanent and continuous formation of teachers; scientific training and scientific evidence in the permanent and continued training of teachers; the role of school management in the permanent and continuous training of teachers; public policy and its relationship with the permanent and continuous training of teachers. The data reveal that the egalitarian and intersubjective dialogue is a fundamental element in the TDPs and contributes to the deepening of the theoretical and scientific bases, giving autonomy and security in the teachers' pedagogical decision-making. The excluding elements reveal that the lack of dialogue with the managers, the bureaucratization and hierarchization of the courses offered and the deviation from the objectives of permanent and continuous formation are factors that create obstacles in the improvement of the formation and education offered. The final analysis between the system and the world of life (HABERMAS, 2012) reveals that the system has promoted this hierarchization and bureaucratization in training at the same time that it can contribute to offering a dialogic training. On the other hand, the world of life is capable of providing answers towards coexistence and permanent and continuous dialogical formation.

La formación permanente y continua de los docentes es un campo de estudio que se relaciona con diferentes áreas del saber a partir de concepciones ideológicas, políticas, sociales, epistemológicas y filosóficas. En este trabajo, los términos: formación permanente y formación continua se utilizan deliberadamente en conjunto para demarcar la posición teórica en Freire (2015). El movimiento de formación basado en la evidencia científica ha aparecido en los informes de organismos internacionales que relacionan directamente la mejora de la educación con la calidad de la formación docente. Demostrada su eficacia en la formación permanente y continua de docentes, la Tertúlia Dialógica Pedagógica (TDP) es una Acción Educativa Exitosa (CREA, 2015) y se muestra como una alternativa viable para la formación dialógica de docentes en Brasil que busca unir con conocimiento científico, promoviendo la mejora en el conocimiento y las relaciones sociales de toda la comunidad escolar. Esta tesis doctoral se fundamenta en la siguiente pregunta de investigación: ¿La Tertúlia Pedagógica Dialógica, como formación dialógica de docentes, puede contribuir y de qué manera a la formación permanente y continuada de docentes basada en evidencias científicas en Brasil? Como objetivo general, analizamos, a través de la transformación o la exclusión de elementos relatados por los participantes de la investigación, cómo la Tertúlia Pedagógica Dialógica puede ser insertada en el contexto de formación permanente y continua de profesores en Brasil, contribuyendo para una formación permanente y continua basada en la ciencia. evidencia. Con base en el marco de la Metodología Comunicativa (GÓMEZ et al., 2006), la investigación involucró un total de 11 profesores de diferentes regiones de Brasil. Para recolectar y profundizar los datos, se realizaron grupos focales e informes comunicativos. La investigación enumeró elementos transformadores y excluyentes en 5 categorías: la formación permanente y continua en el contexto actual de los docentes; el encuentro pedagógico dialógico en la formación permanente y continua de los docentes; formación científica y evidencia científica en la formación permanente y continuada de los docentes; el papel de la dirección escolar en la formación permanente y continua de los docentes; la política pública y su relación con la formación permanente y continua de los docentes. Los datos revelan que el diálogo igualitario e intersubjetivo es un elemento fundamental en los TDP y contribuye a la profundización de las bases teóricas y científicas, dando autonomía y seguridad en la toma de decisiones pedagógicas de los docentes. Los elementos excluyentes revelan que la falta de diálogo con los gestores, la burocratización y jerarquización de los cursos ofrecidos y la desviación de los objetivos de formación permanente y continua son factores que obstaculizan la mejora de la formación y educación ofrecida. El análisis final entre el sistema y el mundo de la vida (HABERMAS, 2012) revela que el sistema ha fomentado esta jerarquización y burocratización en la formación al mismo tiempo que puede contribuir a ofrecer una formación dialógica. Por otra parte, el mundo de la vida es capaz de dar respuestas hacia la convivencia y la formación dialógica permanente y continua.
Pedagogical Dialogic Gathering: permanent teacher training based on scientific evidence
Tertúlia Pedagógica Dialógica: formación docente permanente basada en la evidencia científica
Keywords: Formação continuada de professores; Formação dialógica do professorado; Tertúlia Dialógica Pedagógica; Evidências científicas; Inservice teacher education; Dialogical Pedagogical Gathering; Scientific evidence; Dialogical teacher education; Formación continua del profesorado; Formación dialógica del profesorado; Evidencia científica; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO